Papel das espécies reativas de oxigênio e do óxido nítrico no remodelamento eletromecânico do coração durante a fase aguda da cardiomiopatia chagásica - Artur Santos Miranda (2015)
The infection by Trypanosoma cruzi leads to the development of an intense inflammatory response. Among the consequences of this inflammation, high levels of reactive oxygen species (ROS) and nitric oxide (NO) are produced, which act as important effectors mediating parasites killing and thus the control of infection, but also may cause nonspecific tissue damage under high amounts. Regarding the heart tissue, ROS and NO have been found to regulate the function of many components involved in management of the mechanical and electrical properties of the cardiomyocytes and so as in the excitation-contraction coupling phenomena in these cells. Ergo, it seems reasonable to hypothesize that this reactive molecules production has an important role during the establishment of the cardiomyopathy related to Chagas disease. Therefore, in this study we aimed to investigate the involvement of ROS and NO production and balance in the electromechanical remodeling of the heart during the acute phase of Chagas´ disease. Wild-Type (WT) mice and NADPH phagocyte oxidase-2 (PHOXKO) deficient mice were infected or not with 1000 Y strain T. cruzi i.p. All experiments were performed after 15±1 days of infection (dpi). For cell assays, cardiomyocytes were isolated by perfusing a nutritive solution containing a mix of enzymes through a Langendorff system, followed by mechanical dispersion, in an increasing calcium concentration gradient. We found that PHOXKO 15dpi mice displayed prolonged action potential (AP) repolarization time compared to the other groups, which were similar between themselves. However PHOXKO 15dpi had no changes in calcium and outward potassium currents compared to the controls, in spite of WT 15dpi, which had a reduction in both components. The increase in AP duration (APD) in PHOXKO15dpi was accompanied by increased APD alternans in this group, which has been related to the generation of severe arrhythmias. Such APD alternans was ameliorated by pre-incubation with the NO-synthases inhibitor L-NAME, although the increased APD was remained unchanged. Also, both infected PHOXKO and WT mice exhibited a decreased cell shortening during contraction when compared to the non infected mice, and L-NAME could restore this parameter only in the WT 15dpi group. Also, cardiomyocytes from PHOXKO15dpi displayed higher levels of arrhythmic contractions apart from the field stimulation when compared to other groups, which was fully abolished by exposure to L-NAME. The altered excitability and contractility was associated with reduced calcium transient in PHOXKO 15dpi compared to the other groups, although no difference was observed in the decay phase of the transient. Also the peak transient was not restored by L-NAME. The set of observations at the cellular level reflected in to significant chances in cardiac function studied by the isolated heart technique, despite no significant differences in the systolic tension of the heart between groups. Also PHOXKO 15 dpi mice exhibited high rates of severe arrhythmias in the electrocardiogram and low mean arterial pressure studied by tail plestimography, compared to the other groups. Overall, we conclude that ROS and NO production directly modulates the electromechanical remodeling of the heart during acute phase of chagasic cardiomyopathy.